2006
DOI: 10.1097/01.dad.0000199879.63857.dc
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated Acanthoma With Sebaceous Differentiation

Abstract: Reticulated acanthoma with sebaceous differentiation (RASD) is characterized by the reticulated proliferation of spinous cells with aggregates of mature sebocytes in the bases of the strands of the keratinocytes, often linking rete ridges. Here, we report the first case reported as RASD. A 55-year-old woman presented with a 15-year history of a slightly pruritic patch on the upper back, and the histology was typical for RASD. She had been bothered by a yellow discharge from the tumor. Skin tumors with sebaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…SESD is very closely related to reticulated acanthoma with sebaceus differentiation but is a distinct tumor. Reticulated acanthoma with sebaceous differentiation (RASD) is mainly characterized by proliferation of spinous cells, aggregates of mature sebocytes in the bottom of the strand of epithelium, bridging of the bases of the epithelium by those mature sebocytes and lack of pseudocysts and melanin granules 12,13. Utilizing features like sebaceous aggregates located only at the basal aspects without a reticulated pattern, our case was differentiated from RASD.…”
Section: Discussionmentioning
confidence: 99%
“…SESD is very closely related to reticulated acanthoma with sebaceus differentiation but is a distinct tumor. Reticulated acanthoma with sebaceous differentiation (RASD) is mainly characterized by proliferation of spinous cells, aggregates of mature sebocytes in the bottom of the strand of epithelium, bridging of the bases of the epithelium by those mature sebocytes and lack of pseudocysts and melanin granules 12,13. Utilizing features like sebaceous aggregates located only at the basal aspects without a reticulated pattern, our case was differentiated from RASD.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there has been much speculation about the exact relationship between RASD and MTS. In more recent case reports, Fukai and colleagues and Haake and colleagues, however, performed immunohistochemical staining only for MLH1 and MSH2 protein and concluded that their cases probably had no association with MTS …”
Section: Discussionmentioning
confidence: 99%
“…Reticulated acanthoma with sebaceous differentiation has been defined as a benign proliferation of both keratinocytes and sebocytes, in a reticulated configuration, with acanthosis together with clusters of sebocytes at the bases of rete ridges 2–5 . Apocrine tubular structures are not typically a feature of this entity.…”
Section: Discussionmentioning
confidence: 99%